Using nonword repetition to distinguish genetic and environmental influences on early literacy development: A study of 6-year-old twins - Bishop, D; Adams, C; Norbury, C (2004)
This study considered whether cognitive profile could distinguish groups of children where genes or environment played a major role in influencing reading level. Same-sex twin pairs from an epidemiological study were categorized according to parental report at 4 years of age into those with low language skills and a typically developing group. A total of 132 same-sex twin pairs from the low language group and 66 from the control group were assessed at 6 years of age, to investigate heritability of reading ability adjusted for nonverbal IQ. For pairs where both twins had normal scores on a nonword repetition test, heritability was zero, with environmental influences explaining all the variance. For pairs where one or both twins had low nonword repetition, the heritability estimate was 0.79 and the variance due to shared environment was zero. Future studies of genetics of reading development should treat those with poor nonword repetition skills as a separate subgroup. © 2004 Wiley-Liss, Inc.